Long Run Relationship between Oil Revenue and Economic Growth in Nigeria. - kabir, maryam (Archives of Business Research, 2016)
the paper study the impact oil revenue on Nigeria’s economic growth using Vector Auto Regressive (VAR) model. It was established that oil revenue serve as a major source of foreign earnings, public revenue and budget. Since oil price is determined by demand and supply in the international market any slight change in price affect the revenue. The objective is to examine the effect of oil revenue fluctuations in the Nigerian economy. The type of data used is time series from secondary source. The methodology used to achieve the objective isVector Auto Regressive (VAR)model. It was discovered that the log of oil revenue (OR) is negatively related to the GDP. This means that there is mismanagement of oil revenue in the country. Revenue from oil failed to create linkages to other sectors of the economy .it is therefore recommended that government should provide the necessary infrastructures to diversify the productive base of the economy.